Effect of various sizes extraction of wood -wool on the properties of wood-wool cement board manufactured from Kelampayan (Neolamarckia Cadamba) / Mohd Azrizal Fauzi and Zakiah Ahmad - Fauzi, Mohd Azrizal; Ahmad, Zakiah (Universiti Teknologi MARA Pulau Pinang, 2011)
Kelampayan (Neolamarckia Cadamba) is used in the production of wood-wool cement board (WWCB). The properties of the boards from one type of fast growing timber species were compared by using lower aspect ratio of wood-wool of various sizes (1.5 mm, 2.5 mm and 3.5 mm)with fixed water: cement ratio.